Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

The dolphin FRESH protocol: visual Freshwater-Related Evaluation of Skin Health in free-ranging bottlenose dolphins (Tursiops spp.) - Kristi L. Fazioli; Christina N. Toms; Ryan Takeshita; Alyssa Quackenbush; Denise Greig; Teresa Rowles; Lori Schwacke; Kathleen Colegrove; Ruth Y. Ewing; Deborah Fauquier; Denise Boyd; Aaron Bouwkamp; et al. (Frontiers in Marine Science, 2026)
Exposure to freshwater is a pressing health issue for coastal bottlenose dolphins ( Tursiops spp.). Environmental changes, including increased precipitation events and coastal infrastructure projects, are altering salinity within estuarine systems. Consequently, understanding effects of freshwater exposure on dolphins and developing tools to evaluate related health conditions is urgent. To address this need, a group of veterinarians, pathologists, epidemiologists, natural resource managers, and field biologists convened to create a protocol to visually assess freshwater-related skin lesions in free-ranging bottlenose dolphins. The Dolphin FRESH (Freshwater-Related Evaluation of Skin Health) Protocol guides users without medical backgrounds to screen and evaluate photographs by focusing on the visual identification of three primary indicators of freshwater skin disease: Overgrowth, Target-like Lesions, and Light Discoloration. By determining presence of the primary indicators and scoring associated characteristics, FRESH provides users with a relative assessment of the severity of these skin anomalies, and metrics to track progressive changes. The Scoring Rubric performed well during systematic testing, with evaluators correctly identifying freshwater cases through recognition of primary indicators and with no significant differences in total severity scores between field biologists and medical experts. FRESH is an important step in advancing knowledge on the effects of salinity fluctuations on dolphin health. When applied to photo datasets over time, this tool will enable researchers and managers to evaluate progression and regression of freshwater skin disease, occurrence and effects of multiple exposures, and the relationship between freshwater exposure skin indicators and health and survival outcomes.

Global ocean indicators: Marking pathways at the science-policy nexus - Karina von Schuckmann; Alex Godoy-Faundez; Véronique Garçon; Frank E. Muller-Karger; Karen Evans; Ward Appeltans; Narissa Bax; Lisandro Benedetti Cecchi; Anthony Bernard; Kim Bernard; Jarret Byrnes; Gabrielle Canonico; et al. (Marine Policy, 2026)

Foraminiferal and environmental change across the younger Dryas chronozone, NW Baffin Bay - Stephen J. Culver; David J. Mallinson; Seth R. Sutton; Christopher R. Moore; Allen West; Malcolm A. LeCompte (Quaternary Science Reviews, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Grief Among Oncology Providers: Prevalence and Association with Burnout - Shannon R. McGue; Cameron J. Oswalt; Benjamin T. Berger; Sarah S. Morgan; Sara A. Barlow; Carl F. Pieper; Linda M. Sutton; Matthew K. Labriola; Anthony N. Galanos (Journal of Cancer Education, 2025)

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

Ultrasensitive Staphylococcal Enterotoxin B Quantum Dot-Based Lateral Flow Immunoassays for Rapid Testing of Poultry Rinsates and Milk - Lance P. Ford; Skyler B. Sutton; Daniel R. Mitchell; John G. Bruno (Journal of Fluorescence, 2025)

Separation of virus-like particles and nano-emulsions for vaccine development by Capillary Zone Electrophoresis - Yousef S. Elshamy; Caleb Kinsey; Richard R. Rustandi; Adam T. Sutton (Analytica Chimica Acta, 2025)

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

Toward an integrated pantropical ocean observing system - Gregory R. Foltz; Yassir A. Eddebbar; Janet Sprintall; Antonietta Capotondi; Sophie Cravatte; Peter Brandt; Adrienne J. Sutton; Tamaryn Morris; Juliet Hermes; Clive R. McMahon; Michael J. McPhaden; Lev B. Looney; et al. (Frontiers in Marine Science, 2025)
Global climate is regulated by the ocean, which stores, releases, and transports large amounts of mass, heat, carbon, and oxygen. Understanding, monitoring, and predicting the exchanges of these quantities across the ocean’s surface, their interactions with the atmosphere, and their horizontal and vertical pathways through the global oceans, are key for advancing fundamental knowledge and improving forecasts and longer-term projections of climate, weather, and ocean ecosystems. The existing global observing system provides immense value for science and society in this regard by supplying the data essential for these advancements. The tropical ocean observing system in particular has been developed over decades, motivated in large part by the far-reaching and complex global impacts of tropical climate variability and change. However, changes in observing needs and priorities, new challenges associated with climate change, and advances in observing technologies demand periodic evaluations to ensure that stakeholders’ needs are met. Previous reviews and assessments of the tropical observing system have focused separately on individual basins and their associated observing needs. Here we provide a broader perspective covering the tropical observing system as a whole. Common gaps, needs, and recommendations are identified, and interbasin differences driven by socioeconomic disparities are discussed, building on the concept of an integrated pantropical observing system. Finally, recommendations for improved observations of tropical basin interactions, through oceanic and atmospheric pathways, are presented, emphasizing the benefits that can be achieved through closer interbasin coordination and international partnerships.

The molecular coordination of tuberization: Current status and future directions - Sarah R. Mathura; Fedora Sutton; Judy Rouse-Miller; Valerie Bowrin (Current Opinion in Plant Biology, 2024)

The impact of Nassella trichotoma (Nees) Hack. ex Arechav. on plant diversity, richness and soil properties in South Africa - Anthony Mapaura; Kim Canavan; David M. Richardson; Vincent R. Clark; Guy F. Sutton; Sandy-Lynn Steenhuisen (South African Journal of Botany, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

P06-10 NGS-based discovery of circulating microRNA biomarkers of drug-induced pancreatic injury (DIPI) - P. Szatmary; A. Evans; A. Jones; D. Latawiec; W. Cai; A. Kattakayam; C. Goldring; G. Beyer; S. Sirtl; I. Alvarez-Alvarez; W. Bailey; B. Ackermann; et al. (Toxicology Letters, 2024)

The high-resolution imaging science experiment (HiRISE) in the MRO extended science phases (2009–2023) - A.S. McEwen; S. Byrne; C. Hansen; I.J. Daubar; S. Sutton; C.M. Dundas; N. Bardabelias; N. Baugh; J. Bergstrom; R. Beyer; K.M. Block; V.J. Bray; et al. (Icarus, 2024)

Exploring long-term retention and reactivation of micropollutant biodegradation capacity - Rita H. R. Branco; Roel J. W. Meulepas; Huub H. M. Rijnaarts; Nora B. Sutton (Environmental Science and Pollution Research, 2024)
The factors limiting micropollutant biodegradation in the environment and how to stimulate this process have often been investigated. However, little information is available on the capacity of microbial communities to retain micropollutant biodegradation capacity in the absence of micropollutants or to reactivate micropollutant biodegradation in systems with fluctuating micropollutant concentrations. This study investigated how a period of 2 months without the addition of micropollutants and other organic carbon affected micropollutant biodegradation by a micropollutant-degrading microbial community. Stimulation of micropollutant biodegradation was performed by adding different types of dissolved organic carbon (DOC)—extracted from natural sources and acetate—increasing 10 × the micropollutant concentration, and inoculating with activated sludge. The results show that the capacity to biodegrade 3 micropollutants was permanently lost. However, the biodegradation activity of 2,4-D, antipyrine, chloridazon, and its metabolites restarted when these micropollutants were re-added to the community. Threshold concentrations similar to those obtained before the period of no substrate addition were achieved, but biodegradation rates were lower for some compounds. Through the addition of high acetate concentrations (108 mg-C/L), gabapentin biodegradation activity was regained, but 2,4-D biodegradation capacity was lost. An increase of bentazon concentration from 50 to 500 µg/L was necessary for biodegradation to be reactivated. These results provide initial insights into the longevity of micropollutant biodegradation capacity in the absence of the substance and strategies for reactivating micropollutant biodegrading communities. Graphical abstract

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Identifiability of enzyme kinetic parameters in substrate competition: a case study of CD39/NTPDase1 - Anna N. McGuinness; Aman Tahir; Nadia R. Sutton; Andrew D. Marquis (Purinergic Signalling, 2024)

An analysis of perspectives on groundwater governance arrangements relating to the potential development of unconventional oil and gas in South Africa - Jack R. Hemingway; Alexandra Gormally-Sutton (Hydrogeology Journal, 2024)
An analysis of expert perspectives on groundwater governance arrangements in South Africa is presented, particularly those arrangements that are pertinent to the complex and socially and ecologically significant implications of exploiting unconventional oil and gas (UOG). The paper presents a detailed assessment of literature on groundwater governance research, the findings of which are applied as a framework for a series of expert interviews, comprising hydrogeologists, lawyers, engineers, and governance specialists. This methodological approach was adopted as a means to enable an analysis of opinions on the current situation of groundwater governance in South Africa and how fit-for-purpose this is for managing the exploitation of UOG. The analysis was also informed by observation of participants at several relevant decision-making and stakeholder events. Whilst the findings indicated a generally positive evaluation of the initial steps taken to assess UOG impacts and engage relevant communities, recurrent criticisms also are featured across the interviews. Key implications arising from the research include: (1) the need for continued stakeholder engagement, and government follow-through on the outcomes of these processes, (2) the necessity for detailed groundwater-specific regulations to be drafted at the earliest opportunity, to ensure that the energy policy vacuum does not have a negative knock-on effect for effective groundwater management, and (3) the prevalence of significant governance gaps, particularly regarding regulatory and institutional capacity, and the need for continued development of a functional network of institutions to effectively manage UOG exploitation alongside groundwater resources.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

Estimation of ammonia deposition to forest ecosystems in Scotland and Sri Lanka using wind-controlled NH3 enhancement experiments - Ajinkya G. Deshpande; Matthew R. Jones; Netty van Dijk; Neil J. Mullinger; Duncan Harvey; Robert Nicoll; Galina Toteva; Gothamie Weerakoon; Sarath Nissanka; Buddhika Weerakoon; Maude Grenier; Agata Iwanicka; et al. (Atmospheric Environment, 2024)

Production and preservation of organic carbon in sub-seafloor tephra layers - Jack Longman; Hayley R. Manners; Thomas M. Gernon; James McManus; Martin R. Palmer; Steven J. Rowland; Paul A. Sutton (Marine Chemistry, 2024)

Conserving the evolutionary history of birds - Christopher J. W. McClure; Igor Berkunsky; Evan R. Buechley; Leah Dunn; Jeff Johnson; Jennifer McCabe; Steffen Oppel; Brian W. Rolek; Luke J. Sutton; Rikki Gumbs (Conservation Biology, 2023)
In the midst of the sixth mass extinction, limited resources are forcing conservationists to prioritize which species and places will receive conservation action. Evolutionary distinctiveness measures the isolation of a species on its phylogenetic tree. Combining a species’ evolutionary distinctiveness with its globally endangered status creates an EDGE score. We use EDGE scores to prioritize the places and species that should be managed to conserve bird evolutionary history. We analyzed all birds in all countries and important bird areas. We examined parrots, raptors, and seabirds in depth because these groups are especially threatened and relatively speciose. The three focal groups had greater median threatened evolutionary history than other taxa, making them important for conserving bird evolutionary history. Australia, Brazil, Indonesia, Madagascar, New Zealand, and the Philippines were especially critical countries for bird conservation because they had the most threatened evolutionary history for endemic birds and are important for parrots, raptors, and seabirds. Increased enforcement of international agreements for the conservation of parrots, raptors, and seabirds is needed because these agreements protect hundreds of millions of years of threatened bird evolutionary history. Decisive action is required to conserve the evolutionary history of birds into the Anthropocene.

Standardizing gross descriptions of skin lesions in common bottlenose dolphins (Tursiops truncatus) stranded in Southwest Florida, 2015–2019 - Ruth Y. Ewing; Meghan N. Sutton; Hada M. Herring; Molly R. Schubert; Denise M. Boyd; Jill L. Richardson; David S. Rotstein (Frontiers in Marine Science, 2023)
As the first line of defense, the integumentary system is critical in comprehensively evaluating dolphin morbidity during stranding response. Most published studies on skin lesions in bottlenose dolphins (Tursiops truncatus) lack standardized gross descriptions and methodologies for evaluating lesions. The primary objective of this study was to evaluate the effectiveness of an assessment matrix designed to consistently describe skin lesions based on a set of standardized gross description characteristics. The matrix was implemented by reviewing necropsy reports, histopathology reports, and photographs collected from bottlenose dolphins stranded in Southwest Florida from 2015 through 2019. Of the 32 dolphins that met the inclusion criteria, 19 presented with skin lesions and five reviewers described each of the 46 lesions according to a novel, standardized assessment matrix. The most common descriptor selected, in each of the respective matrix categories, were, by anatomic location, head; distribution, multifocal to coalescing; quantity, moderate (10–30); size, <2 cm; shape, punctate; margin, rounded; color modifier, hyperpigmentation; texture, smooth; and texture modifier, flat. These prevalent descriptors coincided with the frequent occurrence of histologically described hydropic degeneration (n=7, 15.2%) and were confirmed poxviral lesions in 6.52% (n=3). Identifying lesion patterns using standardized descriptors capitalizes on the unique pathogen tissue tropism and the implementation of certain disease mechanisms in the integumentary system. Therefore, it can facilitate differential disease diagnoses and guide ancillary diagnostics testing. The use of standardized descriptors will aid in etiologic identification and monitoring of skin lesions and associated diseases, advancing our understanding of dolphin morbidity and mortality.

Genome-wide Identification of the Auxin Transporter Gene Families in Sweet Potato (Ipomoea batatas) and their Expression During Tuberization - Sarah R. Mathura; Fedora Sutton; Valerie Bowrin (Tropical Plant Biology, 2023)

Increased captures of the critically endangered leatherback turtle (Dermochelys coriacea) around New Zealand: the contribution of warming seas and fisher behavior - Matthew R. Dunn; Brittany Finucci; Matthew H. Pinkerton; Philip Sutton; Clinton A.J. Duffy (Frontiers in Marine Science, 2023)
Five species of sea turtles are known to occur in New Zealand waters, with the leatherback turtle ( Dermochelys coriacea ) being the most frequently reported. In New Zealand all sea turtles are protected, but there are currently no fisheries bycatch mitigation measures. We describe fishery captures of leatherbacks from Ministry observer and fisher self-reported data. A generalized additive model (GAM) was then used to evaluate which factors might explain the observed year trend in captures. Between fishing years 2007–08 and 2020–21 (years starting 1 October), there were 217 captures of leatherback turtles, an annual average of 15.5. Reported captures increased substantially to 50 in 2020–21. Nearly all (97.7%) captures were reported from surface longline fisheries. Because of sparse observer coverage most captures (85.3%) were self-reported by fishers. Within the main fishery, just 9.4% of the vessels reported 94.5% of the leatherback captures, and one vessel reported 40.4% of all captures. Some non-reporting of captures seems likely. The GAM estimated a higher probability of capture with increasing SST from a constant-over-time spatial pattern of monthly sea surface temperature, and predicted the increase in captures in 2020–21. Much of the increase in bycatch could therefore be explained by the fleet moving into warmer areas where the probability of leatherback capture was higher. Capture mitigation measures could include restricting fishing in turtle ‘hotspot’ times and areas. New Zealand waters should be recognized as an important seasonal foraging ground for leatherback turtles where capture mitigation measures are necessary.

Insights from the management of offshore energy resources: Toward an ecosystem-services based management approach for deep-ocean industries - M. Emilia Bravo; Miriam I. Brandt; Jesse M. A. van der Grient; Thomas G. Dahlgren; Patricia Esquete; Sabine Gollner; Daniel O. B. Jones; Lisa A. Levin; Craig R. McClain; Bhavani E. Narayanaswamy; Tracey Sutton; Lissette Victorero; et al. (Frontiers in Marine Science, 2023)
The deep ocean comprises complex ecosystems made up of numerous community and habitat types that provide multiple services that benefit humans. As the industrialization of the deep sea proceeds, a standardized and robust set of methods and metrics need to be developed to monitor the baseline conditions and any anthropogenic and climate change-related impacts on biodiversity, ecosystem function, and ecosystem services. Here, we review what we have learned from studies involving offshore-energy industries, including state-of-the-art technologies and strategies for obtaining reliable metrics of deep-sea biodiversity and ecosystem function. An approach that includes the detection and monitoring of ecosystem services, with open access to baseline data from multiple sectors, can help to improve our global capacity for the management of the deep ocean.

Improving suitability of urban canals and canalized rivers for transportation, thermal energy extraction and recreation in two European delta cities - E. Suzanne van der Meulen; Frans H. M. van de Ven; Pieter R. van Oel; Huub H. M. Rijnaarts; Nora B. Sutton (Ambio, 2023)
Canals and canalized rivers form a major part of surface water systems in European delta cities and societal ambitions to use these waters increase. This is the first assessment of how suitability of these waters can improve for three important uses: transportation, thermal energy extraction (TEE) and recreation. We assess suitability with Suitability Indices (SIs) and identify which alterations in the water system are needed to improve SI scores in Amsterdam, The Netherlands, and Ghent, Belgium. The results show spatial variability in suitability scores. Current suitability for transportation is low (SI score = 1) to excellent (SI score = 4), for TEE fair (SI score = 2) to excellent (SI score = 4), and suitability for recreation is low (SI score = 1). Suitability could improve by enlarging specific waterway dimensions, increasing discharge and clarity, and by enhancing microbiological water quality. The same methodology can be applied to optimize designs for new water bodies and for more water uses.

Advancing best practices for assessing trends of ocean acidification time series - Adrienne J. Sutton; Roman Battisti; Brendan Carter; Wiley Evans; Jan Newton; Simone Alin; Nicholas R. Bates; Wei-Jun Cai; Kim Currie; Richard A. Feely; Christopher Sabine; Toste Tanhua; et al. (Frontiers in Marine Science, 2022)
Assessing the status of ocean acidification across ocean and coastal waters requires standardized procedures at all levels of data collection, dissemination, and analysis. Standardized procedures for assuring quality and accessibility of ocean carbonate chemistry data are largely established, but a common set of best practices for ocean acidification trend analysis is needed to enable global time series comparisons, establish accurate records of change, and communicate the current status of ocean acidification within and outside the scientific community. Here we expand upon several published trend analysis techniques and package them into a set of best practices for assessing trends of ocean acidification time series. These best practices are best suited for time series capable of characterizing seasonal variability, typically those with sub-seasonal (ideally monthly or more frequent) data collection. Given ocean carbonate chemistry time series tend to be sparse and discontinuous, additional research is necessary to further advance these best practices to better address uncharacterized variability that can result from data discontinuities. This package of best practices and the associated open-source software for computing and reporting trends is aimed at helping expand the community of practice in ocean acidification trend analysis. A broad community of practice testing these and new techniques across different data sets will result in improvements and expansion of these best practices in the future.

Comparative biology of the grenadiers Macrourus caml and M. whitsoni in the Ross Sea region, Antarctica - Bradley R. Moore; Steven J. Parker; Peter M. Marriott; Colin Sutton; Matthew H. Pinkerton (Frontiers in Marine Science, 2022)
The grenadiers Macrourus caml and M. whitsoni form a significant bycatch component of longline fisheries for Antarctic toothfish ( Dissostichus mawsoni ) in the Southern Ocean. A lack of species-level biological and catch data has to date hindered the development of quantitative assessments for these deepwater species. This paper examines species- and sex-specific life histories of M . caml and M . whitsoni in the Ross Sea region, Antarctica, from samples collected from the commercial fishery and research collections. Macrourus caml was found to live longer, grow slower, and attain a larger maximum length than M . whitsoni , reaching at least 65 years of age and 97 cm total length (TL) vs. 43 years and 78 cm TL for M . whitsoni . In addition, M . caml attains a larger length for a given age and a greater weight for a given length. For each species, females of a given age were larger and reached a greater maximum age than males. Assuming that selectivity of the fishing gear is related to fish size, greater fishing pressure on females than males is likely, and was evidenced by female-biased sex ratios of both species. Estimates of natural and fishing mortality rates were low for both species. Despite having a shorter lifespan and attaining a smaller maximum length, M . whitsoni matured later in life and at larger lengths than M . caml . Although sampling opportunities are constrained seasonally due to sea ice cover, gonad staging and interannual patterns in gonadosomatic indices suggest prolonged spawning for both species, with available data indicating peak spawning during austral summer. The differences in life history observed between these two closely related and morphologically similar species illustrates the importance of understanding species-specific life histories to infer responses to exploitation, provide key biological inputs to inform parameters for future risk assessments and ecosystem models as well as baseline information for comparative work over both time and space, contribute to greater clarity in managing fisheries that interact with these two species, and further our understanding of grenadier life history.

GeoSoilEnviroCARS (Sector 13) at the Advanced Photon Source: a comprehensive synchrotron radiation facility for Earth science research at ambient and extreme conditions - S. R. Sutton; M. L. Rivers; S. Chariton; P. J. Eng; A. Lanzirotti; M. Newville; T. Officer; V. B. Prakapenka; Y. J. Ryu; J. E. Stubbs; S. Tkachev; Y. Wang; et al. (Physics and Chemistry of Minerals, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Synergistic effects of harvest and climate drive synchronous somatic growth within key New Zealand fisheries - John R. Morrongiello; Peter L. Horn; Caoimhghin Ó Maolagáin; Philip J. H. Sutton (Global Change Biology, 2021)
Fisheries harvest has pervasive impacts on wild fish populations, including the truncation of size and age structures, altered population dynamics and density, and modified habitat and assemblage composition. Understanding the degree to which harvest‐induced impacts increase the sensitivity of individuals, populations and ultimately species to environmental change is essential to ensuring sustainable fisheries management in a rapidly changing world. Here we generated multiple long‐term (44–62 years), annually resolved, somatic growth chronologies of four commercially important fishes from New Zealand's coastal and shelf waters. We used these novel data to investigate how regional‐ and basin‐scale environmental variability, in concert with fishing activity, affected individual somatic growth rates and the magnitude of spatial synchrony among stocks. Changes in somatic growth can affect individual fitness and a range of population and fishery metrics such as recruitment success, maturation schedules and stock biomass. Across all species, individual growth benefited from a fishing‐induced release of density controls. For nearshore snapper and tarakihi, regional‐scale wind and temperature also additively affected growth, indicating that future climate change‐induced warming and potentially strengthened winds will initially promote the productivity of more poleward populations. Fishing increased the sensitivity of deep‐water hoki and ling growth to the Interdecadal Pacific Oscillation (IPO). A forecast shift to a positive IPO phase, in concert with current harvest strategies, will likely promote individual hoki and ling growth. At the species level, historical fishing practices and IPO synergized to strengthen spatial synchrony in average growth between stocks separated by 400–600 nm of ocean. Increased spatial synchrony can, however, increase the vulnerability of stocks to deleterious stochastic events. Together, our individual‐ and species‐level results show how fishing and environmental factors can conflate to initially promote individual growth but then possibly heighten the sensitivity of stocks to environmental change.

Men’s experiences of radiotherapy treatment for localized prostate cancer and its long-term treatment side effects: a longitudinal qualitative study - E. Sutton; J. A. Lane; M. Davis; E. I. Walsh; D. E. Neal; F. C. Hamdy; M. Mason; J. Staffurth; R. M. Martin; C. Metcalfe; T. J. Peters; J. L. Donovan; et al. (Cancer Causes & Control, 2021)
Purpose To investigate men’s experiences of receiving external-beam radiotherapy (EBRT) with neoadjuvant Androgen Deprivation Therapy (ADT) for localized prostate cancer (LPCa) in the ProtecT trial. Methods A longitudinal qualitative interview study was embedded in the ProtecT RCT. Sixteen men with clinically LPCa who underwent EBRT in ProtecT were purposively sampled to include a range of socio-demographic and clinical characteristics. They participated in serial in-depth qualitative interviews for up to 8 years post-treatment, exploring experiences of treatment and its side effects over time. Results Men experienced bowel, sexual, and urinary side effects, mostly in the short term but some persisted and were bothersome. Most men downplayed the impacts, voicing expectations of age-related decline, and normalizing these changes. There was some reticence to seek help, with men prioritizing their relationships and overall health and well-being over returning to pretreatment levels of function. Some unmet needs with regard to information about treatment schedules and side effects were reported, particularly among men with continuing functional symptoms. Conclusions These findings reinforce the importance of providing universal clear, concise, and timely information and supportive resources in the short term, and more targeted and detailed information and care in the longer term to maintain and improve treatment experiences for men undergoing EBRT.

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Trends in Demand of Urban Surface Water Extractions and in Situ Use Functions - E. S. van der Meulen; N. B. Sutton; F. H. M. van de Ven; P. R. van Oel; H. H. M. Rijnaarts (Water Resources Management, 2020)
Scientific literature currently lacks comprehensive understanding of urban surface water use functions. This hampers sound analysis of the demand and potential supply of these functions. This study provides a comprehensive overview of potential use functions, by integrating knowledge from ecosystem services and integrated urban water management fields. Analysis of water-related management plans for Toronto and Amsterdam shows that surface water is currently being used for a variety of functions related to nutrition, energy, water regulation, recreation, symbolic use, transportation and floating buildings. Notably, many use functions involve in situ use, rather than water extractions. Interviewed water managers and spatial planners in both cities expect demand of most use functions to increase by 2040, especially demand for thermal energy extraction, recreation and transportation. Some identified novel demands, such as climate regulation and reuse of waste products from waterway maintenance. Increasing demand is mainly driven by urban growth, climate change and sustainability ambitions. This study found urban surface water uses that are usually not acknowledged in scientific literature on urban water management. This comprehensive overview supports planning, design, and maintenance of urban surface waters, laying the foundation for future research on supply and demand of urban water use functions.

Trophic Structure and Sources of Variation Influencing the Stable Isotope Signatures of Meso- and Bathypelagic Micronekton Fishes - Travis M. Richards; Tracey T. Sutton; R. J. David Wells (Frontiers in Marine Science, 2020)

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Taxonomic Richness and Diversity of Larval Fish Assemblages in the Oceanic Gulf of Mexico: Links to Oceanographic Conditions - Corinne R. Meinert; Kimberly Clausen-Sparks; Maëlle Cornic; Tracey T. Sutton; Jay R. Rooker (Frontiers in Marine Science, 2020)

Oceanographic Structure and Light Levels Drive Patterns of Sound Scattering Layers in a Low-Latitude Oceanic System - Kevin M. Boswell; Marta D’Elia; Matthew W. Johnston; John A. Mohan; Joseph D. Warren; R. J. David Wells; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Covariations between plant functional traits emerge from constraining parameterization of a terrestrial biosphere model - Marc Peaucelle; Cédric Bacour; Philippe Ciais; Nicolas Vuichard; Sylvain Kuppel; Josep Peñuelas; Luca Belelli Marchesini; Peter D. Blanken; Nina Buchmann; Jiquan Chen; Nicolas Delpierre; Ankur R. Desai; et al. (Global Ecology and Biogeography, 2019)
Aim The mechanisms of plant trait adaptation and acclimation are still poorly understood and, consequently, lack a consistent representation in terrestrial biosphere models (TBMs). Despite the increasing availability of geo‐referenced trait observations, current databases are still insufficient to cover all vegetation types and environmental conditions. In parallel, the growing number of continuous eddy‐covariance observations of energy and CO 2 fluxes has enabled modellers to optimize TBMs with these data. Past attempts to optimize TBM parameters mostly focused on model performance, overlooking the ecological properties of ecosystems. The aim of this study was to assess the ecological consistency of optimized trait‐related parameters while improving the model performances for gross primary productivity (GPP) at sites. Location Worldwide. Time period 1992–2012. Major taxa studied Trees and C 3 grasses. Methods We optimized parameters of the ORCHIDEE model against 371 site‐years of GPP estimates from the FLUXNET network, and we looked at global covariation among parameters and with climate. Results The optimized parameter values were shown to be consistent with leaf‐scale traits, in particular, with well‐known trade‐offs observed at the leaf level, echoing the leaf economic spectrum theory. Results showed a marked sensitivity of trait‐related parameters to local bioclimatic variables and reproduced the observed relationships between traits and climate. Main conclusions Our approach validates some biological processes implemented in the model and enables us to study ecological properties of vegetation at the canopy level, in addition to some traits that are difficult to observe experimentally. This study stresses the need for: (a) implementing explicit trade‐offs and acclimation processes in TBMs; (b) improving the representation of processes to avoid model‐specific parameterization; and (c) performing systematic measurements of traits at FLUXNET sites in order to gather information on plant ecophysiology and plant diversity, together with micro‐meteorological conditions.

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

A Surface Ocean CO2 Reference Network, SOCONET and Associated Marine Boundary Layer CO2 Measurements - Rik Wanninkhof; Penelope A. Pickers; Abdirahman M. Omar; Adrienne Sutton; Akihiko Murata; Are Olsen; Britton B. Stephens; Bronte Tilbrook; David Munro; Denis Pierrot; Gregor Rehder; J. Magdalena Santana-Casiano; et al. (Frontiers in Marine Science, 2019)

Statin therapy and herpes virus reactivation—response to Zuin et al. paper - Jonathan E. Sutton; Negar Maghsoodi; Alexa R. Shipman; Kate E. Shipman (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Developing an Integrated Ocean Observing System for New Zealand - Joanne O’Callaghan; Craig Stevens; Moninya Roughan; Chris Cornelisen; Philip Sutton; Sally Garrett; Giacomo Giorli; Robert O. Smith; Kim I. Currie; Sutara H. Suanda; Michael Williams; Melissa Bowen; et al. (Frontiers in Marine Science, 2019)

The Second Warning to Humanity – Providing a Context for Wetland Management and Policy - C. M. Finlayson; Gillian T. Davies; William R. Moomaw; G. L. Chmura; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2019)

Monitoring programs of the U.S. Gulf of Mexico: inventory, development and use of a large monitoring database to map fish and invertebrate spatial distributions - Arnaud Grüss; Holly A. Perryman; Elizabeth A. Babcock; Skyler R. Sagarese; James T. Thorson; Cameron H. Ainsworth; Evan John Anderson; Kenneth Brennan; Matthew D. Campbell; Mary C. Christman; Scott Cross; Michael D. Drexler; et al. (Reviews in Fish Biology and Fisheries, 2018)

Physician Communication Practices as a Barrier to Risk-Based HPV Vaccine Uptake Among Men Who Have Sex with Men - Christopher W. Wheldon; Steven K. Sutton; Holly B. Fontenot; Gwendolyn P. Quinn; Anna R. Giuliano; Susan T. Vadaparampil (Journal of Cancer Education, 2018)

Spatiotemporal heterogeneity and patterning of developing renal blood vessels - Edward Daniel; D. Berfin Azizoglu; Anne R. Ryan; Tezin A. Walji; Christopher P. Chaney; Gabrielle I. Sutton; Thomas J. Carroll; Denise K. Marciano; Ondine Cleaver (Angiogenesis, 2018)

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

Energy expenditure of rugby players during a 14-day in-season period, measured using doubly labelled water - Deborah R. Smith; R. F. G. J. King; L. C. Duckworth; L. Sutton; T. Preston; J. P. O’Hara; B. Jones (European Journal of Applied Physiology, 2018)

Global biogeochemical provinces of the mesopelagic zone - Gabriel Reygondeau; Lionel Guidi; Gregory Beaugrand; Stephanie A. Henson; Philippe Koubbi; Brian R. MacKenzie; Tracey T. Sutton; Martine Fioroni; Olivier Maury (Journal of Biogeography, 2018)
Aim Following the biogeographical approach implemented by Longhurst for the epipelagic layer, we propose here to identify a biogeochemical 3‐D partition for the mesopelagic layer. The resulting partition characterizes the main deep environmental biotopes and their vertical boundaries on a global scale, which can be used as a geographical and ecological framework for conservation biology, ecosystem‐based management and for the design of oceanographic investigations. Location The global ocean. Methods Based on the most comprehensive environmental climatology available to date, which is both spatially and vertically resolved (seven environmental parameters), we applied a combination of clustering algorithms (c‐means, k‐means, partition around medoids and agglomerative with Ward's linkage) associated with a nonparametric environmental model to identify the vertical and spatial delineation of the mesopelagic layer. Results First , we show via numerical interpretation that the vertical division of the pelagic zone varies and, hence, is not constant throughout the global ocean. Indeed, a latitudinal gradient is found between the epipelagic–mesopelagic and mesopelagic–bathypelagic vertical limits. Second, the mesopelagic layer is shown here to be composed of 13 distinguishable Biogeochemical Provinces. Each province shows a distinct range of environmental conditions and characteristic 3‐D distributions. Main conclusions The historical definition of the mesopelagic zone is here revisited to define a 3‐D geographical framework and characterize all the deep environmental biotopes of the deep global ocean. According to the numerical interpretation of mesopelagic boundaries, we reveal that the vertical division of the zone is not constant over the global ocean (200–1,000 m) but varies between ocean basin and with latitude. We also provide evidence of biogeochemical division of the mesopelagic zone that is spatially structured in a similar way than the epipelagic in the shallow waters but varies in the deep owing to a change of the environmental driving factors.

Identification of the ferredoxin interaction sites on ferredoxin-dependent glutamate synthase from Synechocystis sp. PCC 6803 - Masakazu Hirasawa; Jacaranda Solis; Nanditha Vaidyanathan; Anurag P. Srivastava; R. Max Wynn; Roger B. Sutton; David B. Knaff (Photosynthesis Research, 2017)

A 16.7 kb deletion in Sipa1l3 is associated with juvenile cataract in mice - Lianna R. Walker; Emily R. Tosky; Kylee M. Sutton; Rhonda Griess; Marytza D. Abebe; Sarah Y. Barnes; Tom Cunnigham; Stephen D. Kachman; Merlyn K. Nielsen; Daniel C. Ciobanu (Mammalian Genome, 2017)

Influence of oceanographic conditions on abundance and distribution of post‐larval and juvenile carangid fishes in the northern Gulf of Mexico - John A. Mohan; Tracey T. Sutton; April B. Cook; Kevin M. Boswell; R. J. David Wells (Fisheries Oceanography, 2017)
Relationships between abundance of post‐larval and juvenile carangid (jacks) fishes and physical oceanographic conditions were examined in the northern Gulf of Mexico (GoM) in 2011 with high freshwater input from the Mississippi River. Generalized additive models ( GAM s) were used to explore complex relationships between carangid abundance and physical oceanographic data of sea surface temperature ( SST ), sea surface height anomaly ( SSHA ) and salinity. The five most abundant carangid species collected were: Selene setapinnis (34%); Caranx crysos (30%); Caranx hippos (10%); Chloroscombrus chrysurus (9%) and Trachurus lathami (8%). Post‐larval carangids (median standard length [ SL ] = 10 mm) were less abundant during the spring and early summer, but more abundant during the late summer and fall, suggesting summer to fall spawning for most species. Juvenile carangid (median SL = 23 mm) abundance also increased between the mid‐summer and early fall. Most species showed increased abundance at lower salinities and higher temperatures, suggesting entrainment of post‐larval fishes or feeding aggregations of juveniles at frontal convergence zones between the expansive river plume and dynamic mesoscale eddy water masses. However, responses were species‐ and life‐stage specific, which may indicate fine‐scale habitat partitioning between species. Ordination methods also revealed higher carangid abundances at lower salinities for both post‐larval and juvenile life stages, with species‐ and life‐stage specific responses to SST and SSHA , further suggesting habitat separation between species. Results indicate strong links between physical oceanographic features and carangid distributions in the dynamic northern GoM.

Estimating Total Alkalinity in the Washington State Coastal Zone: Complexities and Surprising Utility for Ocean Acidification Research - Andrea J. Fassbender; Simone R. Alin; Richard A. Feely; Adrienne J. Sutton; Jan A. Newton; Robert H. Byrne (Estuaries and Coasts, 2017)

Decadal predictions with the HiGEM high resolution global coupled climate model: description and basic evaluation - L. C. Shaffrey; D. Hodson; J. Robson; D. P. Stevens; E. Hawkins; I. Polo; I. Stevens; R. T. Sutton; G. Lister; A. Iwi; D. Smith; A. Stephens (Climate Dynamics, 2017)

Comparing Chemistry and Census-Based Estimates of Net Ecosystem Calcification on a Rim Reef in Bermuda - Travis A. Courtney; Andreas J. Andersson; Nicholas R. Bates; Andrew Collins; Tyler Cyronak; Samantha J. de Putron; Bradley D. Eyre; Rebecca Garley; Eric J. Hochberg; Rodney Johnson; Sylvia Musielewicz; Tim J. Noyes; et al. (Frontiers in Marine Science, 2016)

QTL and major genes influencing grain yield potential in soft red winter wheat adapted to the southern United States - Christopher K. Addison; R. Esten Mason; Gina Brown-Guedira; Mohammed Guedira; Yuanfeng Hao; Randall G. Miller; Nithya Subramanian; Dennis N. Lozada; Andrea Acuna; Maria N. Arguello; Jerry W. Johnson; Amir M. H. Ibrahim; et al. (Euphytica, 2016)

Recommendations for the future of recreational fisheries to prepare the social‐ecological system to cope with change - R. Arlinghaus; S. J. Cooke; S. G. Sutton; A. J. Danylchuk; W. Potts; K. de M. F. Freire; J. Alós; E. T. da Silva; I. G. Cowx; R. van Anrooy (Fisheries Management and Ecology, 2016)
This paper presents conclusions and recommendations that emerged from the 7th World Recreational Fishing Conference ( WRFC ) held in Campinas, Brazil in September 2014. Based on the recognition of the immense social and economic importance of recreational fisheries coupled with weaknesses in robust information about these fisheries in many areas of the world, particularly in many economies in transition, it is recommended to increase effort to build effective governance arrangements and improve monitoring and assessment frameworks in data‐poor situations. Moreover, there is a need to increase interdisciplinary studies that will foster a systematic understanding of recreational fisheries as complex adaptive social‐ecological systems. To promote sustainable recreational fisheries on a global scale, it is recommended the detailed suggestions for governance and management outlined in the United Nations Food and Agricultural Organization Technical Guidelines for Responsible Fisheries: Recreational Fisheries are followed.

Ustilago echinata: Infection in a Mixed Martial Artist Following an Open Fracture - Ethan Stewart; Sarah Waldman; Deanna A. Sutton; Carmita Sanders; Jonathan Lindner; Hongxin Fan; Nathan P. Wiederhold; George R. Thompson (Mycopathologia, 2016)

A loop unique to ferredoxin-dependent glutamate synthases is not absolutely essential for ferredoxin-dependent catalytic activity - Jatindra N. Tripathy; Masakazu Hirasawa; R. Bryan Sutton; Afia Dasgupta; Nanditha Vaidyanathan; Masoud Zabet-Moghaddam; Francisco J. Florencio; Anurag P. Srivastava; David B. Knaff (Photosynthesis Research, 2015)

A Direct Pre-screen for Marine Bacteria Producing Compounds Inhibiting Quorum Sensing Reveals Diverse Planktonic Bacteria that are Bioactive - Jamie S. Linthorne; Barbara J. Chang; Gavin R. Flematti; Emilio L. Ghisalberti; David C. Sutton (Marine Biotechnology, 2015)

The Grain of Spatially Referenced Economic Cost and Biodiversity Benefit Data and the Effectiveness of a Cost Targeting Strategy - N. J. SUTTON; P. R. ARMSWORTH (Conservation Biology, 2014)
Facing tight resource constraints, conservation organizations must allocate funds available for habitat protection as effectively as possible. Often, they combine spatially referenced economic and biodiversity data to prioritize land for protection. We tested how sensitive these prioritizations could be to differences in the spatial grain of these data by demonstrating how the conclusion of a classic debate in conservation planning between cost and benefit targeting was altered based on the available information. As a case study, we determined parcel‐level acquisition costs and biodiversity benefits of land transactions recently undertaken by a nonprofit conservation organization that seeks to protect forests in the eastern United States. Then, we used hypothetical conservation plans to simulate the types of ex ante priorities that an organization could use to prioritize areas for protection. We found the apparent effectiveness of cost and benefit targeting depended on the spatial grain of the data used when prioritizing parcels based on local species richness. However, when accounting for complementarity, benefit targeting consistently was more efficient than a cost targeting strategy regardless of the spatial grain of the data involved. More pertinently for other studies, we found that combining data collected over different spatial grains inflated the apparent effectiveness of a cost targeting strategy and led to overestimation of the efficiency gain offered by adopting a more integrative return‐on‐investment approach.

Summer Movements of the Gulf Killifish (Fundulus grandis) in a Northern Gulf of Mexico Salt Marsh - T. Reid Nelson; Deionta Sutton; Dennis R. DeVries (Estuaries and Coasts, 2014)

Considering “Coastal Carbon” in Existing U.S. Federal Statutes and Policies - Linwood H. Pendleton; Ariana E. Sutton-Grier; David R. Gordon; Brian C. Murray; Britta E. Victor; Roger B. Griffis; Jen A.V. Lechuga; Chandra Giri (Coastal Management, 2013)

Constraints on the partitioning of Kīlauea’s lavas between surface and tube flows, estimated from infrared satellite data, sulfur dioxide emission rates, and field observations - W. C. Koeppen; M. Patrick; T. Orr; A. J. Sutton; D. Dow; R. Wright (Bulletin of Volcanology, 2013)

Illustrating the critical role of human dimensions research for understanding and managing recreational fisheries within a social‐ecological system framework - L. M. Hunt; S. G. Sutton; R. Arlinghaus (Fisheries Management and Ecology, 2013)
Effective management of recreational fishing requires understanding fishers and their actions. These actions constitute critical links between social and ecological systems that result in outcomes that feedback and influence recreational fishers' actions and the management of these actions. Although much research exists on recreational fishers and their actions, this research is often disconnected from management issues. One way to help to overcome this disconnect is to illustrate how past research on the social component of recreational fishing fits within an emerging coupled social‐ecological system ( SES ) framework. Herein, a conceptual SES is first developed with specific attention to recreational fisheries. This SES is then used to illustrate the importance of considering human dimensions research for articulating, studying and ultimately managing key outcomes of recreational fisheries (e.g. fish population conservation, fisher well‐being) using the example of harvest regulations and a brief review of past interdisciplinary research on recreational fishing. The article ends by identifying key research needs including understanding: how factors such as management rules affect the diversity of actions by recreational fishers; how governance and management approaches adapt to changing social and resource conditions; and how recreational fishers learn and share information.

A verification framework for interannual-to-decadal predictions experiments - L. Goddard; A. Kumar; A. Solomon; D. Smith; G. Boer; P. Gonzalez; V. Kharin; W. Merryfield; C. Deser; S. J. Mason; B. P. Kirtman; R. Msadek; et al. (Climate Dynamics, 2013)

The impact of resolution on the adjustment and decadal variability of the Atlantic meridional overturning circulation in a coupled climate model - Daniel L. R. Hodson; Rowan T. Sutton (Climate Dynamics, 2012)

Polymorphic variants in tenascin-C (TNC) are associated with atherosclerosis and coronary artery disease - Mollie A. Minear; David R. Crosslin; Beth S. Sutton; Jessica J. Connelly; Sarah C. Nelson; Shera Gadson-Watson; Tianyuan Wang; David Seo; Jeffrey M. Vance; Michael H. Sketch; Carol Haynes; Pascal J. Goldschmidt-Clermont; et al. (Human Genetics, 2011)

Are deep‐sea demersal fish assemblages globally homogenous? Insights from seamounts - Malcolm R. Clark; Franziska Althaus; Alan Williams; Edwin Niklitschek; Gui M. Menezes; Nils‐Roar Hareide; Philip Sutton; Ciaran O’Donnell (Marine Ecology, 2010)
Deep‐sea fishes have been poorly sampled globally, and overall knowledge of demersal fish distributions and the drivers of community composition and diversity remain limited. Here, we used nine comparable datasets with species‐level identification of fishes from research surveys around the world to test the hypothesis that deep‐sea demersal fish assemblage composition on seamounts is consistent between major oceans. Two levels of analysis were undertaken: the first combined all presence‐absence data from a seamount, while a second more detailed analysis included catch weight data based on a smaller number of seamounts. Overall, there was a consistent separation of seamounts by region based on the compositions of their fish assemblages. New Zealand and SE Australian seamounts have a very similar ichthyofauna, which differs substantially from seamounts in the eastern South Pacific Ocean off Chile. In the North Atlantic, Bear Seamount appears to be distinct from all others, while seamount fish assemblages off Ireland, the Azores, and Faraday Seamount have some affinities. The Tasman Sea and New Caledonian seamounts show strong intra‐regional variation. On an ocean basin scale we therefore reject the hypothesis that the composition of deep‐sea demersal fish fauna is homogeneous globally. However, regional patterns of both species composition and relative abundance show some similarities between widely separated geographical locations, especially where orange roughy is a dominant species. Salinity was the main environmental factor identified in a multivariate analysis of environmental covariate data. This is likely to be a result of salinity being a key characteristic defining both Antarctic Intermediate Water and North Atlantic Deep Water, the water masses found over most seamounts examined in this study, and which may explain similarities between deep‐sea fish assemblages.

Climate impacts of recent multidecadal changes in Atlantic Ocean Sea Surface Temperature: a multimodel comparison - Daniel L. R. Hodson; Rowan T. Sutton; Christophe Cassou; Noel Keenlyside; Yuko Okumura; Tianjun Zhou (Climate Dynamics, 2010)

Effects of Restored Stream Buffers on Water Quality in Non-tidal Streams in the Choptank River Basin - Adrienne J. Sutton; Thomas R. Fisher; Anne B. Gustafson (Water, Air, & Soil Pollution, 2010)

In vitro and in vivo characterization of JNJ-31020028 (N-(4-{4-[2-(diethylamino)-2-oxo-1-phenylethyl]piperazin-1-yl}-3-fluorophenyl)-2-pyridin-3-ylbenzamide), a selective brain penetrant small molecule antagonist of the neuropeptide Y Y2 receptor - James R. Shoblock; Natalie Welty; Diane Nepomuceno; Brian Lord; Leah Aluisio; Ian Fraser; S. Timothy Motley; Steve W. Sutton; Kirsten Morton; Ruggero Galici; John R. Atack; Lisa Dvorak; et al. (Psychopharmacology, 2010)

Development of a low-cost system for measuring conditional time-averaged gradients of SO2 and NH3 - D. Famulari; D. Fowler; E. Nemitz; K. J. Hargreaves; R. L. Storeton-West; G. Rutherford; Y. S. Tang; M. A. Sutton; K. J. Weston (Environmental Monitoring and Assessment, 2010)

Comparison of Outcomes of Permanently Closed and Periodically Harvested Coral Reef Reserves - C. Y. BARTLETT; C. MANUA; J. CINNER; S. SUTTON; R. JIMMY; R. SOUTH; J. NILSSON; J. RAINA (Conservation Biology, 2009)
In many areas of the developing world, the establishment of permanent marine reserves is inhibited by cultural norms or socioeconomic pressures. Community conserved areas that are periodically harvested are increasingly being implemented as fisheries management tools, but few researchers have empirically compared them with permanently closed reserves. We used a hierarchal control‐impact experimental design to compare the abundance and biomass of reef fishes, invertebrates, and substrate composition in periodically harvested and permanent reserves and in openly fished (control sites) of the South Pacific island country of Vanuatu. Fished species had significantly higher biomass in periodically harvested reserves than in adjacent openly fished areas. We did not detect differences in substratum composition between permanent reserves and openly fished areas or between permanent reserves and periodically harvested reserves. Giant clams (tridacnids) and top shells (Trochus niloticus) were vulnerable to periodic harvest, and we suggest that for adequate management of these species, periodically harvested community conservation areas be used in conjunction with other management strategies. Periodic harvest within reserves is an example of adaptive and flexible management that may meet conservation goals and that is suited to the social, economic, and cultural contexts of many coastal communities in the developing world .

The N-glycolyl form of mouse sialyl Lewis X is recognized by selectins but not by HECA-452 and FH6 antibodies that were raised against human cells - Junya Mitoma; Tatsuo Miyazaki; Mark Sutton-Smith; Misa Suzuki; Hideo Saito; Jiunn-Chern Yeh; Takehiro Kawano; Ole Hindsgaul; Peter H. Seeberger; Maria Panico; Stuart M. Haslam; Howard R. Morris; et al. (Glycoconjugate Journal, 2009)

A review of climate risk information for adaptation and development planning - R. L. Wilby; J. Troni; Y. Biot; L. Tedd; B. C. Hewitson; D. M. Smith; R. T. Sutton (International Journal of Climatology, 2009)
Although the use of climate scenarios for impact assessment has grown steadily since the 1990s, uptake of such information for adaptation is lagging by nearly a decade in terms of scientific output. Nonetheless, integration of climate risk information in development planning is now a priority for donor agencies because of the need to prepare for climate change impacts across different sectors and countries. This urgency stems from concerns that progress made against Millennium Development Goals (MDGs) could be threatened by anthropogenic climate change beyond 2015. Up to this time the human signal, though detectable and growing, will be a relatively small component of climate variability and change. This implies the need for a twin‐track approach: on the one hand, vulnerability assessments of social and economic strategies for coping with present climate extremes and variability, and, on the other hand, development of climate forecast tools and scenarios to evaluate sector‐specific, incremental changes in risk over the next few decades. This review starts by describing the climate outlook for the next couple of decades and the implications for adaptation assessments. We then review ways in which climate risk information is already being used in adaptation assessments and evaluate the strengths and weaknesses of three groups of techniques. Next we identify knowledge gaps and opportunities for improving the production and uptake of climate risk information for the 2020s. We assert that climate change scenarios can meet some, but not all, of the needs of adaptation planning. Even then, the choice of scenario technique must be matched to the intended application, taking into account local constraints of time, resources, human capacity and supporting infrastructure. We also show that much greater attention should be given to improving and critiquing models used for climate impact assessment, as standard practice. Finally, we highlight the over‐arching need for the scientific community to provide more information and guidance on adapting to the risks of climate variability and change over nearer time horizons (i.e. the 2020s). Although the focus of the review is on information provision and uptake in developing regions, it is clear that many developed countries are facing the same challenges. Copyright © 2009 Royal Meteorological Society

Historical Changes in Water Quality at German Branch in the Choptank River Basin - Adrienne J. Sutton; Thomas R. Fisher; Anne B. Gustafson (Water, Air, & Soil Pollution, 2009)

Exploring multi-model atmospheric GCM ensembles with ANOVA - D. L. R. Hodson; R. T. Sutton (Climate Dynamics, 2008)

Quasi-periodic fluctuations in the Greenland–Iceland–Norwegian Seas region in a coupled climate model - Sonia R. Gamiz-Fortis; Rowan T. Sutton (Ocean Dynamics, 2007)

Predicting yellow toadflax infestations in the Flat Tops Wilderness of Colorado - Jason R. Sutton; Thomas J. Stohlgren; K. George Beck (Biological Invasions, 2007)

The Nightsat mission concept - C. D. Elvidge; P. Cinzano; D. R. Pettit; J. Arvesen; P. Sutton; C. Small; R. Nemani; T. Longcore; C. Rich; J. Safran; J. Weeks; S. Ebener (International Journal of Remote Sensing, 2007)

On the climate response of the low-latitude Pacific Ocean to changes in the global freshwater cycle - P. D. Williams; E. Guilyardi; R. T. Sutton; J. M. Gregory; G. Madec (Climate Dynamics, 2006)

Chemical Signal Mediated Premating Reproductive Isolation in a Marine Polychaete, Neanthes acuminata (Arenaceodentata) - R. Sutton; E. Bolton; H. D. Bartels-Hardege; M. Eswards; D. J. Reish; J. D. Hardege (Journal of Chemical Ecology, 2005)

Economics of Intensively Managed Forest Plantations in the Pacific Northwest - Glen E. Murphy; Wink R. J. Sutton; Denny Hill; Charles Chambers; Dennis Creel; Clark Binkley; David New (Journal of Forestry, 2005)
Lower risks and higher returns favor investment in intensively managed forest plantations in the Pacific Northwest (PNW) for industrial landowners. Intensive forest plantation management is necessary if PNW industrial landowners are to compete effectively in world markets. However, not all landowner classes have the same set of management objectives, investment streams, and performance measures. For a variety of reasons, intensive forest plantation management may not be appropriate for some nonindustrial and public lands.

Passive hinge forces in the feeding apparatus of Aplysia aid retraction during biting but not during swallowing - G. P. Sutton; J. B. Macknin; S. S. Gartman; G. P. Sunny; R. D. Beer; P. E. Crago; D. M. Neustadter; H. J. Chiel (Journal of Comparative Physiology A, 2004)

An intercomparison between the surface heat flux feedback in five coupled models, COADS and the NCEP reanalysis - C. Frankignoul; M. Botzet; A. F. Carril; E. Kestenare; H. Drange; A. Pardaens; L. Terray; R. Sutton (Climate Dynamics, 2004)

Variability in North Atlantic heat content and heat transport in a coupled ocean-atmosphere GCM - Dong B.; Sutton R. (Climate Dynamics, 2002)

In vivo glycosylation of MUC1 in airway epithelial cells - Howard S. Silverman; Mark Sutton-Smith; Paul Heal; Simon Parry; Timea Palmai-Pallag; Shih-Hsing Leir; Howard R. Morris; Anne Dell; Ann Harris (Glycoconjugate Journal, 2002)

Genetic Relationship of Tumor-Associated Piscine Retroviruses - Sandra L. Quackenbush; Joel Rovnak; Rufina N. Casey; Thomas A. Paul; Paul R. Bowser; Claudia Sutton; James W. Casey (Marine Biotechnology, 2001)

FAB-MS characterization of sialyl Lewisx determinants on polylactosamine chains of human airway mucins secreted by patients suffering from cystic fibrosis or chronic bronchitis - Willy Morelle; Mark Sutton-Smith; Howard R. Morris; Monique Davril; Philippe Roussel; Anne Dell (Glycoconjugate Journal, 2001)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Cuticular hydrocarbons of Glossina austeni and G. pallidipes: Similarities between populations - D. A. Carlson; B. D. Sutton; U. R. Bernier (International Journal of Tropical Insect Science, 2000)

Effects of electrical stimulation leg training during the acute phase of spinal cord injury: a pilot study - Regina M. Crameri; Adele R. Weston; Sue Rutkowski; James W. Middleton; Glen M. Davis; John R. Sutton (European Journal of Applied Physiology, 2000)

The seasonal cycle of tropical Pacific sea surface temperature in a coupled GCM - J. Thuburn; R. T. Sutton (Climate Dynamics, 2000)

Influence of gelling agents on culture medium gel strength, water availability, tissue water potential, and maturation response in embryogenic cultures of Pinus strobus L. - K. Klimaszewska; M. bernier-Cardou; D. R. Cyr; B. C. S. Sutton (In Vitro Cellular & Developmental Biology - Plant, 2000)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

The Role of Guesswork in Conserving the Threatened Sand Skink - Earl D. McCoy; Phillip E. Sutton; Henry R. Mushinsky (Conservation Biology, 1999)
Because we possess little understanding of what constitutes optimal habitat for the threatened sand skink, any individual charged with choosing among habitat fragments to promote recovery of the species will need to employ some guesswork. We examined the relative values of employing two kinds of guesswork, “uneducated guesswork,” from literature descriptions of optimal habitat, and “educated guesswork,” from expert judgments of optimal habitat. The rank order of seven areas of scrub habitat in central Florida based on abundance of the sand skink ( Neoseps reynoldsi ) was compared with the rank order of the areas based on literature descriptions and on expert judgments. Ranks of areas based on expert judgments predicted ranks of areas based on sand skink abundance much better than did ranks of areas based on literature descriptions. Our results show, on the one hand, how uneducated guesswork could challenge recovery of the sand skink and, on the other hand, how educated guesswork could support its recovery.

Elution Patterns from Capillary GC for Methyl-Branched Alkanes - David A. Carlson; Ulrich R. Bernier; Bruce D. Sutton (Journal of Chemical Ecology, 1998)

A late Holocene pollen record of deforestation and environmental change from the Lake Tauanui catchment, Northland, New Zealand - M. B. Elliot; J. R. Flenley; D. G. Sutton (Journal of Paleolimnology, 1998)

The East Auckland Current, 1994–95 - Basil R. Stanton; Philip J. H. Sutton; Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 1997)
The East Auckland Current (EAUC) was investigated in 1994–95 using data from three CTD surveys (conductivity, temperature, depth) and moored current meters. The strength and position of the EAUC was found to be highly variable with most of the current re‐circulating around an anticyclonic eddy north‐east of North Cape—the North Cape Eddy. The position and intensity of this eddy changed resulting in complex flow patterns with a south‐east flowing EAUC not always present as a contiguous feature. The current meter data showed a high level of mesoscale variability with low spatial coherence, suggesting that the along shore correlation length scale was c. 100 km in this current system. Near North Cape, a persistent but variable counter‐current was found inshore of the EAUC. To the south‐east a permanent anticyclonic East Cape Eddy found north of East Cape appears to dominate the flow field and the genesis of the East Cape Current.

Effects of acute expansion of plasma volume on cardiovascular and thermal function during prolonged exercise - S. M. Grant; H. J. Green; S. M. Phillips; J. R. Sutton (European Journal of Applied Physiology, 1997)

Basis of the 1:1 stoichiometry of the high affinity receptor FcεRI-IgE complex - M. B. Keown; R. Ghirlando; G. A. Mackay; B. J. Sutton; H. J. Gould (European Biophysics Journal, 1997)

Blood metabolite and catecholamine responses to prolonged exercise following either acute plasma volume expansion or short-term training - R. Helyar; H. Green; D. Zappe; J. Sutton (European Journal of Applied Physiology, 1997)

Identification and analysis of an alcelaphine herpesvirus 1 (AHV-1) cDNA clone expressing a fusion protein recognized by AHV-1-neutralizing antisera - R. S. Lahijani; S. M. Sutton; R. B. Klieforth; W. P. Heuschele (Archives of Virology, 1995)

Bovine cutaneous papillomas associated with bovine papillomavirus type 5 - N. Bloch; R. H. Sutton; P. B. Spradbrow (Archives of Virology, 1994)

Operation Everest II: An indication of deterministic chaos in human heart rate variability at simulated extreme altitude - Yoshiharu Yamamoto; Richard L. Hughson; John R. Sutton; Charles S. Houston; Allen Cymerman; Ernest L. Fallen; Marked V. Kamath (Biological Cybernetics, 1993)